2012
DOI: 10.1088/0957-4484/23/49/495306
|View full text |Cite
|
Sign up to set email alerts
|

Nanoepitaxy of GaAs on a Si(001) substrate using a round-hole nanopatterned SiO2mask

Abstract: GaAs is grown by metal-organic vapor-phase epitaxy on a 55 nm round-hole patterned Si substrate with SiO2 as a mask. The threading dislocations, which are stacked on the lowest energy facet plane, move along the SiO2 walls, reducing the number of dislocations. The etching pit density of GaAs on the 55 nm round-hole patterned Si substrate is about 3.3 × 105 cm−2. Compared with the full width at half maximum measurement from x-ray diffraction and photoluminescence spectra of GaAs on a planar Si(001) substrate, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…In direct GaAs-on-Si epitaxy with an abrupt transition from the substrate to the overgrown GaAs, a two-step method [30] is widely adopted to improve the structural perfection of the hetero-epitaxial thin ilms. Post-growth thermal cycle annealing [40][41][42], by which an epilayer is subjected to large temperature oscillations and thus periodically switching between compressed and tensile states [43], has been found effective in reducing threading dislocation densities. Insertion of dislocation ilter layers, such as a strained layer superlattice [44] or thin strained layers [45], can facilitate the annihilation of threading dislocations thereby minimize intrusion of dislocations in the active layers of interest.…”
Section: Wafer-scale Hetero-epitaxial Growth Of Iii-v Thin Ilms On Simentioning
confidence: 99%
“…In direct GaAs-on-Si epitaxy with an abrupt transition from the substrate to the overgrown GaAs, a two-step method [30] is widely adopted to improve the structural perfection of the hetero-epitaxial thin ilms. Post-growth thermal cycle annealing [40][41][42], by which an epilayer is subjected to large temperature oscillations and thus periodically switching between compressed and tensile states [43], has been found effective in reducing threading dislocation densities. Insertion of dislocation ilter layers, such as a strained layer superlattice [44] or thin strained layers [45], can facilitate the annihilation of threading dislocations thereby minimize intrusion of dislocations in the active layers of interest.…”
Section: Wafer-scale Hetero-epitaxial Growth Of Iii-v Thin Ilms On Simentioning
confidence: 99%
“…The first challenge is the lattice mismatch between silicon and gallium arsenide (4.1%), which induces the formation of crystalline defects to accommodate the strain in the material. To reduce crystalline defects density, various smart improvements have been investigated like post-growth thermal cycle annealing, 2,8 insertion of dislocation filter layer, 9 selective growth in trenches using aspect ratio trapping (ART) method [10][11][12] or Ge/GeSi buffer layer. 13 The second challenge is the difference of thermal expansion coefficients between Si and III-V (6.6 × 10 −6 K −1 and 2.3 × 10 −6 K −1 for GaAs and Si, respectively), which limits the film thickness before crack appears.…”
mentioning
confidence: 99%
“…resulting for a GaAs top layer thickness of 1 μm [54] still exceeds the value achieved with ART growth of GaAs using a SiO 2 cylinder hole mask [48] (Section 2.1.3.2).…”
Section: Defect Filtering By Multiple Quantum Dot Layersmentioning
confidence: 79%
“…Despite this benefit, ART with cylinder hole masks has been investigated only by few research groups [48][49][50]. Hsu et al [48] reported the MOVPE growth of smooth continuous 900 nm thick GaAs layers of low defect density on Si(001) substrate patterned with a round nanohole SiO 2 mask having a hole diameter of 55 nm and aspect ratio of 4.7. Like in the case of ART trenches, threading misfit defects were confined to the lower part of the holes, giving monocrystalline, relaxed GaAs in the upper part and a very low etch pit density of 3.3 × 10 5 cm…”
Section: Growth On Surfaces Patterned With a Cylinder Hole Maskmentioning
confidence: 99%
See 1 more Smart Citation